PENGEMBANGAN POTENSI WISATA SEJARAH DAN KEARIFAN LOKAL MASYARAKAT SOASIO MELALUI PROGRAM PAKET WISATA DAN RUMAH BUDAYA SEBAGAI PUSAT KESULTANAN TIDORE - Sosmiarti Sosmiarti; Ubpa Aprilia Fahlefi (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Soasio is a village located in the City of Tidore Islands. Soasio has historical tourism that must be developed because it has excellent potential. The development of historical tourism potential is also carried out by preserving local wisdom in the Soasio area, which is still being carried out by the Soasio people. The development of historical tourism potential and local wisdom is carried out with the concept of a tour package called Heritage Travel Tour. This tour package will be done by visiting 7 historical tourist attractions in Soasio. This activity will empower Soasio and work together with the Office of Culture and Tourism of the City of Tidore Islands, which can be accessed through the travel application. The concept of the Cultural House can also be used as a center for learning Tidore culture in Soasio and practice and display various traditions of the Soasio people. This activity is carried out by interview, observation, and documentation methods. The concept of the Heritage Travel Tour and the House of Culture will help preserve the local culture and introduce culture to tourists who come to visit and help the region's income.